Communication Behaviour of Dairy Farmers in Hilly Areas - R. P. Sahu N. K. Singh and M. P. Singh, (Indian Journal of Extension Education, 2014)
The present study was conducted during 2013 in the Bageshwar district of Uttarakhand. Six villages namely Karala,Pasdev, Tana, Bhatkhola, Matela and Kholseer were selected randomly. From each village 20 farmers were selected. Thestudy revealed that most potential information sources were personal localite channels as the extent use of these channelswas 59.60 per cent. Whereas, farmers used mass media and personal cosmopolite channels up to 47.55 and 44.33 per cent,respectively for obtaining the information on recommended dairy technology. Over all data shows that among the varioussources of information, neighbours (75.00%), progressive farmers (73.33%), television (71.66%), local leader (60.00%),SMS/Scientist (58.33%) and radio (56.66%) were mostly used by the farmers to obtain information for betterment ofdairy farming.